Experimental study on rheological properties and moisture susceptibility of asphalt mastic containing red mud waste as a filler substitute. (30th June 2019) - Zhang, Jizhe; Sun, Changjun; Li, Peizhao; Liang, Ming; Jiang, Hongguang; Yao, Zhanyong
Highlights: Red mud increased the shearing deformation resistance of asphalt mastic. Red mud increased the stiffness and elastic behavior of asphalt mastic. Incorporating hydrated lime can improve the moisture resistance of aggregate-mastic interfaces containing red mud. Abstract: This paper investigates the feasibility to improve the rheological behavior and moisture resistance of asphalt mastic prepared with the red mud waste, which is generated from the alumina refining industry. In order to recognize the efficiency of red mud as a mineral filler, three different filler materials, including limestone, hydrated lime and fly ash, were selected and compared. The experimental methods, including Rotating Viscometer, Dynamic Shear Rheometer (DSR), bonding strength evaluation were conducted to evaluate the rheological properties of asphalt mastics and their bonding behavior with different aggregate substrates in both dry and wet conditions. The experimental results showed that the replacement of limestone filler by red mud increased the viscosity of asphalt mastic and the addition of hydrated lime further improved its viscosity. The red mud thus increased the stiffness and elastic behavior of the corresponding asphalt mastic, which in turn has a potential to improve the rutting resistance of the modified asphalt mixtures. However, the use of red mud can reduce the moisture resistance of the aggregate-mastic bonding layer. When further incorporating a certain amount of hydrated lime, this can provide a solution to improve the moisture resistance. Therefore, a tailored and integrated replacement of limestone filler by using the red mud and hydrated lime can be promoted to obtain comparable performance as that of the limestone filler.